2023
DOI: 10.58962/ht.2023.1.3.19-28
|View full text |Cite
|
Sign up to set email alerts
|

Mobile games in the training process of football players 5-6 years old

Iryna Sobko,
Mykyta Dovbnia,
Vitalii Franshchuk

Abstract: Rationale and purpose The high emotionality of mobile games, as well as the simplicity and naturalness of the motor content, are effective means and methods widely used in sports. The purpose of the study is to develop and substantiate the use of mobile games for the development of the physical abilities of young football players. Material and Methods Participants of the research are athletes (boys) of the early development football academy of the “Equator” shopping center, Kharkiv, number 28, age 5-6 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There is no doubt, these characteristics are of particular importance in other sports, such as football, where logical thinking, as well as physical strength and endurance are essential for success [12]. Speed qualities, endurance, strength and agility help to successfully apply technical techniques and implement tactical tasks during the game [13].…”
Section: висновкиmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt, these characteristics are of particular importance in other sports, such as football, where logical thinking, as well as physical strength and endurance are essential for success [12]. Speed qualities, endurance, strength and agility help to successfully apply technical techniques and implement tactical tasks during the game [13].…”
Section: висновкиmentioning
confidence: 99%
“…On the other hand, high physical activity, especially during distance learning, is the basis of integral development of elementary school children, since good physical fitness contributes to the development of the intellectual and emotional spheres [14]. In particular, the involvement of young football players of 5-6 years old in interesting outdoor games formed the basic physical qualities and motor skills of athletes [13]. Jylänki P. and co-authors also showed that physical activity and fundamental motor skills enhanced cognitive abilities and academic performance of children aged 3-7 years [Jylänki,et al,15], while combining mathematics lessons with physical exercises significantly improved intellectual abilities and motor skills of elementary school children [16].…”
Section: висновкиmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the player to control his body well (Sobko et al, 2023). As with many things, practice and repetition are key to improving soccer passing accuracy.…”
Section: Introductionmentioning
confidence: 99%